A review of artificial intelligence applications in apparel industry. Issue 3 (4th March 2022) - Noor, Abid; Saeed, Muhammad Asad; Ullah, Tehseen; Uddin, Zia; Ullah Khan, Raja Muhammad Waseem
Abstract: Nowadays apparel industries face ever-increasing global competition and unpredictable variations in demand. These pressures force manufacturers to consistently improve the efficiency of their manufacturing process to produce the finished product within the most reasonable timeline and the lowest cost of production. However, under a complex and fuzzy manufacturing environment, optimal, and consistent solutions are difficult to obtain. Consequently, in response to the need for new methods, a significant (steadily increasing) number of initiatives have sought to explore and optimize the use of artificial intelligence (AI) techniques in a range of industrial applications. This article demonstrates that research is still limited on AI application in the apparel industry by examining and analyzing the limitations of research challenges and previous studies. This article also addresses the problems facing the implementation of AI technologies in the apparel industry.